Obesity, youth quality of life and competency development - Rodriguez, Adriana Maria Ortega; Krauss, Steven Eric; Abdullah, Haslinda; Ismail, Ismi Arif (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
According to the available data from the Institute for Public Health (NHMS III 2006) 5.4% of children younger than 18 years old in Malaysia were either overweight or obese. Being overweight or obese has detrimental effects on individual health and wellbeing and serious repercussions in terms of economic and social costs for a young, developing nation such as Malaysia. Children and teens that are overweight or obese face increased health problems; and suffer from social stigmatization, poor self-image, and depression. And as overweight and obese children get older they will be at risk of developing eating disorders, and/or becoming addicted to substance abuse. Thus, the negative impact of overweightness and obesity can spill over to society and derail the country’s economic plans of becoming a fully developed nation. The literature reviewed uncovered queries about the possibility of Malaysian youth being affected by health risks related to obesity and the impact on their quality of life; as well as the question of whether health competency development could contribute towards health promotion and improvement in youth quality of life as well as positively contribute towards Nation development.